Giant bezoar causing recurrent abdominal pain in a young girl with autism spectrum disorder - Paolo Quitadamo; Giusy Ranucci; Stefania Ragozzino; Sonia Tamasi; Marcella Giugliano; Giovanni Gaglione; Daniele De Brasi; Augusto Mastrominico; Giovanni Di Nardo (Elsevier, 2022)
A giant bezoar fulfilling the stomach, the duodenum and the jejunum for about 60-70 cm was found in a young girl with autism spectrum disorder, admitted for acute abdominal pain. At initial radiological evaluation an intestinal ilea-ileal intussusception was diagnosed but a computed tomography showed hypointense material with a chambered aspect likely due to accidental ingestion of exogenous material. The presence of a giant bezoar was endoscopically confirmed and the patient underwent surgery for its manual removal.